2009
DOI: 10.3928/01484834-20090515-07
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Strategies for Teaching Evidence-Based Practice in Accelerated Second-Degree Programs

Abstract: An important challenge for teaching in accelerated second-degree programs is how to manage essential content within a compressed curriculum format. This article describes a project that used a collaborative model for teaching evidence-based practice (EBP) in a redesigned second-degree nursing program. Instructors in two courses shared responsibility for teaching basic concepts and guiding students' implementation of EBP in a clinical setting in partnership with clinical nurses. This approach resulted in a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 7 publications
3
30
0
11
Order By: Relevance
“…Many studies have been conducted regarding the effectiveness of including EBP principles in the primary nursing education curriculum. [26][27][28] However, more research needs to be conducted regarding the education of nurses who did not receive evidence-based education in their primary nursing education program. Little evidence was found that examined the effectiveness of including EBP instruction during employee orientation or mandatory educational sessions.…”
Section: Recommendationsmentioning
confidence: 97%
“…Many studies have been conducted regarding the effectiveness of including EBP principles in the primary nursing education curriculum. [26][27][28] However, more research needs to be conducted regarding the education of nurses who did not receive evidence-based education in their primary nursing education program. Little evidence was found that examined the effectiveness of including EBP instruction during employee orientation or mandatory educational sessions.…”
Section: Recommendationsmentioning
confidence: 97%
“…Bondmass (2007) and Corder (2007) taught the principles and process of evidence‐based approach to senior nursing students in a baccalaureate nursing program to achieve a better understanding in students, so that they value research evidence. Kruszewski et al . (2009) also used collaborative strategies for teaching evidence‐based practice in accelerated second‐degree programs.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Bondmass (2007) and Corder (2007) taught the principles and process of evidence-based approach to senior nursing students in a baccalaureate nursing program to achieve a better understanding in students, so that they value research evidence. Kruszewski et al (2009) also used collaborative strategies for teaching evidence-based practice in accelerated seconddegree programs. McAllister (2001) provided the opportunity for academic staff to consider the best ways to integrate evidence-based nursing into nursing education by development of a new undergraduate nursing curriculum.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Hvor grundig laeringsaktivitetene ble beskrevet varierte i de inkluderte studiene. De fleste kombinerte forelesninger og/eller e-laering med påfølgende oppgaveløsning (20)(21)(22)(23)(24)(26)(27)(28)(29). En studie (20) undersøkte effekten av et interaktivt undervisningsopplegg i KBP over ett semester mot slutten av utdanningen.…”
Section: Aksjonsforskningunclassified
“…Gruppearbeid Åtte artikler (20)(21)(22)(23)(24)(26)(27)(28) beskrev at studentene arbeidet i grupper hvorav seks beskrev en gruppestørrelse fra fire til seks deltakere (20-23, 26,28). En av artiklene beskrev gruppesammensetning på tvers av emner og nivåer (22).…”
Section: Aksjonsforskningunclassified